AB0954 IS CONNECTIVE TISSUE MASSAGE EFFECTIVE IN INDIVIDUALS WITH FIBROMYALGIA?. (2nd June 2020) - Keskin, A.; Basakci Calik, B.; Gur Kabul, E.; Cobankara, V.
Abstract : Background: Fibromyalgia (FM) is a systemic rheumatic disease characterized by diffuse pain in the body, tenderness, fatigue and many more symptoms. Exercise is effective and safe method in individuals with FM. Connective tissue massage, another treatment method, is a reflex therapy where shear force is applied in a certain order at the connective tissue interfaces of the skin. In the literature, there is limited study releted compared with clinical pilates exercises and connective tissue massage in individuals with FM. Objectives: The aim of the study was to examine the effectiveness of clinical pilates exercises and connective tissue massage in Individuals with Fibromyalgia on disease activity, number of painful regions, anxiety, biopsychosocial status and quality of life. Methods: 32 women (age mean=52.43±8.32) diagnosed with FM according to American College of Rheumatology (ACR) criteria were included in this study. Participants were randomly divided into two groups as interventional group (n=15, mean age=48.80±7.48) and control group (n=17, mean age=55.64±7.87). While the connective tissue massage and clinical pilates exercises were applied to the treatment group, only clinical pilates exercises were applied to the control group. After the demographic characteristics and disease related data of the individuals were recorded; number of painful regions were assessed with Pain Location Inventory (PLI), disease impact with Fibromyalgia Impact Questionnare (FIQ), functional status with Health Assessment Questionnare (HAQ), anxiety with Beck Anxiety Inventory (BAI), quality of life with Short Form-36 (SF-36) and biopsychosocial status with Cognitive Exercise Therapy Approach (BETY) Scale were evaluated. All evaluations were made before and after treatment. All interventions were applied 3 days per week for 6 weeks by the same experienced physical therapist. One session for clinical pilates exercises consisted of 60 minutes (10 minutes warm up, 40 minutes clinical pilates exercises, 10 minutes cool-down). Connective tissue massage was started from lumbosacral region and continued lower thoracic, scapular, interscapular, and cervical regions, respectively. The Kolmogorov-Smirnov Test was used to determine whether the continuous variables were normal distributions. Results: When the pre-treatment and post-treatment results are analyzed; the results were significant in the intervention group of PLI (p = 0.007), SF 36 physical component (p = 0.025) and mental component (p = 0.017) and FIQ (p = 0.004), while in the control group the difference in SF 36 physical component (p = 0.008) and mental component (p = 0.024), FIQ (p = 0.001) and BAI (p = 0.043) was significant. Delta values were calculated by subtracting post-treatment results from pre-treatment results. When the delta values of the groups are compared, it was determined that the difference only in the PLI (p = 0.023) were significant in favor of the treatment group. Conclusion: According to our results, connective tissue massage has been shown to be effective in reducing the number of painful areas in addition to the positive effects of clinical pilates exercises in individuals with FM. In order to increase the effectiveness of treatment in individuals with FM, we recommend the use of connective tissue massage as an additional treatment method. References: [1]Busch, Angela J., et al. Exercise therapy for fibromyalgia. Current pain and headache reports 2011;15: 358. [2]Burckhardt CS. Nonpharmacologic management strategies in fibromyalgia. Rheumatic diseases clinics of North America, 2002, 28(2), 291-304. Disclosure of Interests: None declared